Mitochondrial Haplogroups Are Associated With Risk of Neuroretinal Disorder in HIV-Positive Patients - Hendrickson, Sher L. (2010)
Although highly active antiretroviral therapy has improved survivorship dramatically and decreased the incidence of cytomegalovirus retinitis among patients with AIDS, other ophthalmic complications continue to occur. One complication observed in ~12% of HIV-infected patients is a presumed neuroretinal disorder (NRD), manifested as decreased contrast sensitivity and associated with vague subjective complaints of hazy vision. Pathologically, patients with AIDS even without ocular opportunistic infections have loss of optic nerve axons, suggestive of mitochondrial dysfunction. We explored whether variation in mitochondrial DNA was associated with time to NRD in HIV-infected patients in the Longitudinal Study of Ocular Complications of AIDS cohort. Within the Western European, or “N”, mitochondrial DNA macrohaplogroup, haplogroup J, was associated with 80% decrease in the risk of progression to NRD during the study (hazard ratio = 0.20, P = 0.039) and suggested an independent association with protection against NRD in a cross-section of all patients taken at enrollment (1.5% vs. 8.9% in patients with vs. without haplogroup J, respectively, P = 0.05). These data suggest that mitochondrial genotype may influence propensity to develop HIV-associated NRD in patients with AIDS.